Energy harvesting for efficient 5G networks - Mukhlif, F.; Al-Gumaei, Y.A.; Noordin, K.A. (2018)
The design of traditional mobile wireless network emphasises on large capacity as well as ubiquitous access. However, environmental protection and energy saving may soon become inevitable trends due to rising global demands. In the wireless networking field, researchers should shift their focus towards efficient networks and energy harvesting (EH). In this work, we consider energy efficiency and EH to address the issue of energy shortage, which also represents the ratio of the quantity of data that have been transferred to the dissipated energy within the system, simultaneously. The simulation-based mathematics signifies the relation between energy efficiency (